2017
DOI: 10.1038/s41598-017-17828-7
|View full text |Cite
|
Sign up to set email alerts
|

Dual repression of endocytic players by ESCC microRNAs and the Polycomb complex regulates mouse embryonic stem cell pluripotency

Abstract: Cell fate determination in the early mammalian embryo is regulated by multiple mechanisms. Recently, genes involved in vesicular trafficking have been shown to play an important role in cell fate choice, although the regulation of their expression remains poorly understood. Here we demonstrate for the first time that multiple endocytosis associated genes (EAGs) are repressed through a novel, dual mechanism in mouse embryonic stem cells (mESCs). This involves the action of the Polycomb Repressive Complex, PRC2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Embryonic stem cells (ESCs) isolated from the inner cell mass of the blastocyst represent a wonderful model system to follow developmental decisions and cell fate transitions in vitro (Evans, 2011, Evans and Kaufman, 1981, Martin, 1981). Recent reports have demonstrated that endocytosis plays a role in regulating the acquisition, as well as the maintenance of the pluripotent state (Dambournet et al., 2018, Li et al., 2010, Mote et al., 2017, Qin et al., 2014, Subramanyam et al., 2011). Endocytosis is a fundamental eukaryotic process, wherein membrane-bound proteins are trafficked to different compartments of the cell depending on their function, with the help of small GTPases called RABs (Doherty and McMahon, 2009, Traub, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic stem cells (ESCs) isolated from the inner cell mass of the blastocyst represent a wonderful model system to follow developmental decisions and cell fate transitions in vitro (Evans, 2011, Evans and Kaufman, 1981, Martin, 1981). Recent reports have demonstrated that endocytosis plays a role in regulating the acquisition, as well as the maintenance of the pluripotent state (Dambournet et al., 2018, Li et al., 2010, Mote et al., 2017, Qin et al., 2014, Subramanyam et al., 2011). Endocytosis is a fundamental eukaryotic process, wherein membrane-bound proteins are trafficked to different compartments of the cell depending on their function, with the help of small GTPases called RABs (Doherty and McMahon, 2009, Traub, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the binding of anionic SAα2‐6Gal‐ and SAα2‐3Gal‐SFNPs was increased in PrECs. Genes related to multiple endocytosis are repressed in mouse ESCs, and the suppression is weakened during differentiation; this might enhance uptake of anionic SFNPs through the endocytic process. Furthermore, CD44, which is a hyaluronate receptor and increases during differentiation, might be involved in increasing the binding potency of anionic SFNPs .…”
Section: Resultsmentioning
confidence: 99%
“…PRC2 and miRNAs were recently shown to independently corepress endocytosis genes in mESCs (Mote et al 2017). To test if miRNAs and PRC2 repressed a common set of genes independently in GBM cells, we depleted miRNAs globally by overexpressing VP55 in EZH2 −/− T98G cells and performed miRNA-seq and mRNA-seq.…”
Section: Mirnas Repress Hundreds Of Genes Directly Repressed By Prc2mentioning
confidence: 99%